Impact of reducing complement inhibitor binding on the immunogenicity of native neisseria meningitidis outer membrane vesicles - Daniels-Treffandier, H; de Nie, K; Marsay, L; Dold, C; Sadarangani, M; Reyes-Sandoval, A; Langford, P; Wyllie, D; Hill, F; Pollard, A; Rollier, C (Public Library of Science, 2016)
Neisseria meningitidis recruits host human complement inhibitors to its surface to down-regulate complement activation and enhance survival in blood. We have investigated whether such complement inhibitor binding occurs after vaccination with native outer membrane vesicles (nOMVs), and limits immunogenicity of such vaccines. To this end, nOMVs reactogenic lipopolysaccharide was detoxified by deletion of the lpxl1 gene (nOMVlpxl1). nOMVs unable to bind human complement factor H (hfH) were generated by additional deletions of the genes encoding factor H binding protein (fHbp) and neisserial surface protein A (NspA) (nOMVdis). Antibody responses elicited in mice with nOMVdis were compared to those elicited with nOMVlpxl1 in the presence of hfH. Results demonstrate that the administration of human fH to mice immunized with fHbp containing OMVlpxl1 decreased immunogenicity against fHbp (but not against the OMV as a whole). The majority of the OMV-induced bactericidal immune response (OMVlpxl1 or OMVdis) was versus PorA. Despite a considerable reduction of hfH binding to nOMVdis, and the absence of the vaccine antigen fHbp, immunogenicity in mice was not different from nOMVlpxl1, in the absence or presence of hfH (serum bactericidal titers of 1:64 vs 1:128 after one dose in the nOMVdis and nOMVlpxl1–immunized groups respectively). Therefore, partial inhibition of fH binding did not enhance immunity in this model.